Pengaruh Investasi UMKM dan Piutang Qardh Terhadap Modal Kerja UMKM Dalam Unit Usaha Syariah Di Indonesia - Septi Nirmia Utamy (AGHNIYA : Jurnal Ekonomi Islam, 2022)
The purpose of this research is to see, know and analyze the influence of MSME (Micro, Small and Medium Enterprises) Investment and Qardh Receivables on MSME Working Capital in Sharia Business Units in Indonesia. The research methode used is quanttitative research analysis. This study was analyzed using the SPSS application, namely descriptive statistical methods, classical assumption test, multiple linear regression tests, hypothesis testing and coefficient of determination. The population in this study is all quarterly financial report data on Financing in Sharia Busniness Units from 2016 to 2020 which has been found in Sharia Banking Statistics (SPS). While the sample in this study is MSME Investment and Qardh Receivables. The result of the Ftest hypothesis stated that the value of Fcount Ftable (19.129 3.16) and the significance level of 0.000 0.05. then the hypothesis Ha is accepted and Ho is rejected, which meand that there is a positive and significant influence jointly from all independent variables on the supporting variables. The result of the Coefficient of Determination test show that the R-Square value is 0.678 or 67.8%. This means that 67.8% of the value of MSME Investment and Qardh Receivables affects MSME Working Capital in UUS. While the remaining 32.2% is influenced by other variables thar are not included.